A Comprehensive Approach to Midface Rejuvenation: Our Philosophy, Algorithm, and Surgical Technique - Lee, Daniel D.; Lee, Kathryn W.; Williams, Edwin F., III (Facial Plastic Surgery, 2021)
With a greater understanding of the aging process and relevant anatomy, the facial plastic surgeon has an expansive armamentarium of options for midface rejuvenation. Upon reflection, our practice has evolved over the years and only recently found a select number of interventions that have consistently produced excellent results. In this article, we discuss the steps needed to establish an effective patient relationship, present an algorithm on how to approach midface rejuvenation, describe our surgical technique, and review the attributes and liabilities of each procedure.
Keywords: midface rejuvenation; deep plane facelift; volume rejuvenation; fat grafting; subperiosteal midface lift